A baffling referral from dermatology- aleukemic leukemia cutis with literature review - Swamy, Shruthi; Angadi, Veerendra; I. Nandennavar, Manjunath; Karpurmath, Shashidhar V. (International Journal of Research in Medical Sciences, 2024)
Aleukemic leukemia cutis (ALC) is a rather uncommon condition that is characterized by leukemic cell invasion into the skin which primarily precedes the peripheral blood and marrow infiltration by leukemic cells. We present a 35-year-old male with maculopapular skin lesions with a normal bone marrow and peripheral smear. Skin lesions were positive for leukemic cells. Bone marrow infiltration was identified 1 month after the skin diagnosis which showed Acute Myeloid leukemia with Monocytic differentiation. The patient succumbed to tumor lysis syndrome before initiation of treatment. ALC portends a very poor prognosis. Prompt diagnosis with skin biopsy is essential to improve survival in ALC.